Effect of cadmium on the growth and antioxidant enzymes in two varieties of Brassica juncea - Irfan, Mohd (2013)
Increasing contamination and higher enrichment ratio of non-essential heavy metal cadmium (Cd) induce various toxic responses in plants when accumulated above the threshold level. These effects and growth responses are genotype and Cd level dependent. An experiment was conducted to analyze the effect of Cd toxicity in Brassica juncea [L] Czern and Coss by selecting its two varieties Varuna and RH-30. Cadmium (0, 25, 50 or 100 mg CdCl(2) kg(−1) of soil) fed to soil decreased the values of growth characteristics, activity of nitrate reductase and leaf water potential, whereas activities of antioxidant enzymes and proline content increased with the increasing concentration of Cd, observed at 30 and 60 day stages of growth, in both the varieties. Moreover, Cd uptake by the roots was higher in RH-30 than Varuna. Also the activity of antioxidant enzymes and proline accumulation were higher in Varuna with increasing soil level of Cd. Out of the two varieties, Varuna was more tolerant than RH-30 to Cd stress.